OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY OF RETINAL VENOUS OCCLUSION. Issue 11 (November 2015) - Kashani, Amir H.; Lee, Sun Young; Moshfeghi, Andrew; Durbin, Mary K.; Puliafito, Carmen A.
Abstract : Purpose: To noninvasively evaluate the retinal microvasculature in human subjects with retinal venous occlusions using optical coherence tomography angiography and assess potential clinical applications. Methods: This was a prospective, observational study of adult human subjects with clinical and imaging findings demonstrating retinal venous occlusion. Subjects underwent complete ophthalmic examination and fluorescein angiography as appropriate for their standard of care. Optical coherence tomography angiography was performed on a prototype spectral domain-OCTA system in 3 mm × 3 mm and 6 mm × 6 mm regions centered on the fovea and parafoveal areas. Retinal vasculature was assessed within three horizontal slabs consisting of the superficial, middle, and deep retina. The vasculature within each slab was reconstructed using intensity contrast-based algorithms and visualized as en-face images. Optical coherence tomography angiograms were manually segmented to verify the accuracy of the automated segmentation algorithms. Results: Optical coherence tomography angiography was able to demonstrate almost all of the clinically relevant findings in 25 subjects with acute and chronic retinal venous occlusion. These findings were consistent with clinical, anatomic, and fluorescein angiographic findings including areas of impaired vascular perfusion, retinal atrophy, vascular dilation, shunt vessels, and some forms of intraretinal edema. Conclusion: Optical coherence tomography angiography is an investigational method that generates high-resolution, noninvasive angiograms that qualitatively illustrate most of clinically relevant findings in retinal venous occlusion. Optical coherence tomography angiography corresponds well with fluorescein angiograms and in many cases provides more detailed anatomic and blood flow information. Optical coherence tomography angiography, in conjunction with standard spectral domain-OCT, is at least equally as effective as fluorescein angiography for evaluation and management of the macular complications of retinal venous occlusions. Abstract : Optical coherence tomography angiography generates high-resolution, noninvasive angiograms that illustrate almost all clinically relevant findings in retinal venous occlusion. Optical coherence tomography angiography corresponds well with fluorescein angiograms and in many cases provides more detailed anatomic and blood flow information. Depth encoded optical coherence tomography angiography images allowed localization of vascular lesions to either the superficial or mid-retinal layers and in many cases both layers.